Determinants of Investment Decision Through Sharia Financial Technology - Novianti, Fitria; Syamlan, Yaser Taufik (Sekolah Tinggi Agama islam Negeri Majene, 2024)
The level of investment through Islamic Peer-to-Peer (P2P) Lending ascends. This study aims to determine the direct effect of perceived behavioural control, perceived benefit, perceived easiness, and perceived risk on investment decision through sharia peer-to-peer lending. The further purpose is to find out the indirect effect of perceived behavioural control, attitude toward investment, and subjective norm on investment decision through sharia peer-to-peer lending intervened by investment intention. Through primary data distributed using online questionnaire to residents who live in Indonesia and investing through Sharia Financial technology peer-to-peer lending platform, final sample was 135 respondents. The data analysis technique used is Structural Equation Modelling Partial Least Square (SEM-PLS). The result of this study finds that there is a significant effect on the perceived behavioural control, perceived easiness, and perceived risk on investment decision through sharia peer-to-peer lending while the insignificant effect of sharia compliance and perceived benefit on investment decision through sharia peer-to-peer lending has been found. Subsequently, perceived behavioural control, attitude toward investment, and subjective norm have no effect at all on investment decision through sharia peer-to-peer lending intervened by investment intention.